A diatom-based palaeoclimatic reconstruction for the border of Leribe-Makhotlong-Butha-Buthe Districts, Eastern Lesotho Highlands - Ncube, Lungile (My University, 2021)
The eastern Lesotho highlands presents an important site for palaeoenvironmental research in southern Africa, as it represents a niche environment which is enriched with a unique biodiversity and characterised by distinct climatic patterns strongly influenced by topography. Lesotho, with its montane wetlands, is invaluable to southern Africa as these form part of the Senqu-Orange River headwaters, one of the most important rivers draining the subcontinent. The region of Lesotho is also characterised by susceptibility to climate change and variability, moreover, the economy and livelihoods of communities in Lesotho depend on the environment. This presents a further need to better understand past climatic and environmental change at a higher spatio-temporal resolution, such information can be used to inform adaptation strategies to cope with the long-term effects of climate change. Although highly resolved reconstructions exist for the region, they are mostly clustered along the eastern escarpment, whereas this study focused on samples from the understudied northern region of Lesotho. Therefore, this study represents the first Holocene palaeoenvironmental reconstruction in the far northern part of the eastern Lesotho highlands. The reconstruction generated from this study is therefore developed from the diatoms and sediment analyses, which were performed on sediment cores from two high altitudinal wetland sites in the vicinity of the Afriski resort, with the first site being BLMA (~3,108 m.asl) and the second site, BLMB (~2,996 m.asl). The age of the sites were temporally constrained, spanning 4,200cal yr BP for site BLMA and 1,450 cal. yr BP for site BLMB, based on Accelerator Mass Spectrometer (AMS) dating. The proxies used in this study indicate fluctuations between wet and dry conditions. ~4,200 –3,200 cal yr BP is characterised by a wet period which is gradually progressed by a dry period at ~2,980 –2,410 cal yrs. BP.~2,400 –1,145 cal yr BP is a wet period and another wet period begins for the region at ~1,145 –750 cal yr BP with much warmer conditions that the previous wet period. At ~700 –450 cal yr BP a dry period occurs and finally at ~400 cal yr BP –present day the diatoms suggest a wet period and a cold event ~200 cal yr BP. The results of this study indicate some similarities with other records from eastern Lesotho (Mafadi and Sekhokhong) and from palaeoenvironmental sites (Braamhoek and Ntsikeni Wetland) in South Africa. For comparisons on a global scale, the record shows evidence, or signals of the occurrence of global climatic events such as the ‘4.2 kyr’ event, the ‘2.8 kyr’ event, the Little Ice Age (LIA)and the Medieval Warming Period (MWP)
A dissertation submitted to the Faculty of Science in fulfilment of the requirements for a Master of Science degree at the School of Geography, Archaeology and Environmental Studies University of the Witwatersrand, 2021